Diagnostic disclosure to parents of children with developmental disabilities: Experiences and communication preferences - Zeynal Yasacı; İpek Yeldan (Anatolian Journal of Health Research, 2026)
Aim: Communication during developmental disability diagnosis disclosure may influence parents’ emotional responses, understanding, and engagement with care. This study investigated parents’ experiences and preferences regarding disclosure and their evaluations of the communication behaviors of the person who initially communicated the diagnosis. Methods: This descriptive cross-sectional web-based survey was conducted between July and November 2020 with 95 parents of children diagnosed with developmental disabilities. A semi-structured questionnaire assessed demographic characteristics, disclosure experiences and preferences, and perceived communication behaviors. Findings were summarized using descriptive statistics. Results: The most common diagnoses were Down syndrome (22.1%), cerebral palsy (17.9%), and intellectual disability/developmental delay (16.9%). Most parents reported physician-led disclosure (73.7%), whereas 93.7% preferred disclosure by a physician. More than half received the diagnosis in a crowded or shared room (52.6%), while 93.7% preferred a private room. In addition, 31.6% reported receiving inadequate information about their child’s medical condition and treatment, and 35.8% stated that the person who initially communicated the diagnosis did not adequately recognize their emotional distress.Conclusion: Group-level distributions of reported experiences and stated preferences differed descriptively across several aspects of disclosure. The findings indicate areas requiring attention, particularly privacy, information provision, and emotional sensitivity. Because individual-level concordance was not analyzed, these results should not be interpreted as demonstrating within-parent mismatch. Improving privacy, empathy, clarity of information, and post-diagnostic guidance may enhance parental satisfaction and support engagement with care.